2011
DOI: 10.4238/vol10-2gmr967
|View full text |Cite
|
Sign up to set email alerts
|

Cox-2 gene polymorphism and IL-6 levels in coronary artery disease

Abstract: ABSTRACT. Coronary artery disease is one of the leading causes of mortality and diabetes mellitus is one of its main risk factors due to microvascular and macrovascular complications, such as atherosclerosis. Atherosclerosis is now known to be an inflammatory process mediated by prostaglandins and several interleukins. As both are important in inflammatory processes, we examined Cox-2 (-765G > C) polymorphism and interleukin-6 levels in coronary artery disease patients compared to healthy controls. We also div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…A possible reason for the discrepancy is that the clinical role of COX-2 in inflammation may be dual by initiating the process of inflammation and then later aiding in its resolution. The effects of COX-2 genotypes in the inflammatory response through variations in COX-production have been shown with relation to C-reactive protein [32] and IL-6 [34]. In particular, PEG2 is important in regulating IL-6 production and COX-2 inhibitors have been shown to be useful in controlling fibroblast IL-6 production.…”
Section: Discussionmentioning
confidence: 99%
“…A possible reason for the discrepancy is that the clinical role of COX-2 in inflammation may be dual by initiating the process of inflammation and then later aiding in its resolution. The effects of COX-2 genotypes in the inflammatory response through variations in COX-production have been shown with relation to C-reactive protein [32] and IL-6 [34]. In particular, PEG2 is important in regulating IL-6 production and COX-2 inhibitors have been shown to be useful in controlling fibroblast IL-6 production.…”
Section: Discussionmentioning
confidence: 99%
“…The response rate is almost identical to what has been observed in the pivotal phase III study with adalimumab where 71% of patients achieved PASI 75. 10 Atherosclerosis is an inflammatory disease [13][14][15][16][17][18][19] and patients with different clinical atherosclerotic manifestations are faced with persistent vascular risk despite our current armamentarium. Anti-inflammatory therapies are presently being assessed to reduce further the risk of myocardial infarction and stroke of patients with established vascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…More recent studies on the effect of rs1800795 on transcription factor binding have shown that -174G>C transversion gates the GATA1 access to IL-6 promoter, thereby linking this single nucleotide polymorphism (SNP) to differential risk of inflammation-related diseases such as prostate cancer (Cole et al, 2010). Several of the polymorphisms located in the IL-6 promoter region have also been studied in various disease conditions, i.e., coronary artery disease, asthma, rectal cancer, neuroblastoma, and juvenile arthritis (Corvol et al, 2009; Lagmay et al, 2009; Slattery et al, 2009; Ol et al, 2011). The effect of IL-6 promoter haplotype (-597G>A, -572G>C and -174G>C) has also been shown to have a significant effect on transcriptional regulation and disease association (Cussigh et al, 2011).…”
Section: Introductionmentioning
confidence: 99%